UPAYA PENGELOLA KELOMPOK BERMAIN DALAM MENEMPUH AKREDITASI LEMBAGA SESUAI STANDAR NASIONAL PENDIDIKAN - Safuri Musa; Rita Uthartianty; Sri Nurhayati (Universitas Singaperbangsa Karawang, 2020)
The background of this research problem is that less than 5% of the 121,895 Playgroup institutions in West Java are accredited. This identifies that the implementation of the Play Group is not yet in accordance with the national education standards. The purpose of this study is to describe the efforts and obstacles of the management of the Anak Mulia Play Group in Cibogo Village, Lembang District, West Bandung Regency in taking accreditation as an effort to improve the quality of implementation according to national education standards. The research method used in this research is descriptive qualitative with a case study approach. The conclusion of this research is that Playgroup managers show that: (1) managers need serious efforts, by mobilizing their resources, including energy, costs, time, funds and conducting intensive mentoring to fellow Play Group institution that have successfully achieved accreditation institutions, and (2) the obstacles experienced by managers are the limited ability to fill in accreditation data online, the lack of order in documenting the implementation of Play Groups, limited operational funds for the institution and not fully understand the contents of the National Education Standards document